Improving Graphene Conductivity through Selective Atomic Layer Deposition. (10th September 2015) - Liu, Chanyuan; Han, Xiaogang; Bao, Wenzhong; Pearse, Alexander J; Hu, Liangbing; Rubloff, Gary W
Abstract : We present a method to electrically heal and connect graphene flakes via selective atomic layer deposition (ALD) of conductive materials. Selective growth of conductive materials is observed on graphene cracks and edges but exhibits a significant nucleation barrier on intact basal planes due to the chemical inertness. Self-assembled graphene flake films have 10X conductivity after selective platinum (Pt) ALD. In addition, a graphene field effect transistor (FET) model system is used to monitor graphene carrier density and mobility variation after ALD growth. Selective ALD of other conductive materials is also discussed.